PERILAKU IBU DALAM PENANGANAN KEP PADA ANAK BALITA DI PUSKESMAS NGEMPLAK SIMONGAN SEMARANG - Sukesi Niken (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Mother represent especial and first perpetrator to child. One of the problems at under 5 year is the happening of lacking of habit or nutrient recognized by lacking of protein energi which is on condition is and conceived of by heavy of ugly nutrient, and if taking place along of growth trouble and growth. Governmental during the time in hand lacking of protein energi only gyrating feeding of addition and counselling of health pass by Posyandu or Puskesmas whereas family take care of and under 5 year looking after not yet too signalized so that handling of case lacking of longer protein energi. Target of research in general is to comprehend behavioral phenomenon of mother in handling lacking of protein energi at its child of him. Research qualitative with approach of fenomologis done to mother having child of under 5 year with lacking of protein energi in Semarang Ngemplak Simongan Puskesmas. Amount of sampel at this research counted 5 (five) mother and its intake of him use technique of purposive sampling. Data collecting technique with indepth interview, technique analyse and use analysis domain. Result of research of indication that behavior of mother which consist of knowledge, attitude and behavior of indication that with its positive behavior it him mother can detection early to lacking of protein energi and also handling lacking of protein energi real correct and good. Where this behavior is influenced by social and environmental factor of culture, storey; level education of mother, many or often mother contact with media print, radio, and television.Keyword : Behavioral of mother, Handling lacking of protein energi, child of under 5 year